1991
DOI: 10.1007/bf00196501
|View full text |Cite
|
Sign up to set email alerts
|

Electrotropism of pollen tubes of camellia and other plants

Abstract: Pollen tubes of Camellia japonica grew toward the cathode upon exposure to an electric field. Reversal of the field direction during the course of tube growth also reversed the direction of tube growth. These observations demonstrate the existence of the electrotropism of pollen tubes. This electrotropic response was confirmed in several kinds of pollen. The direction that the growing tube turned was found to differ with different pollen species, but it did not vary in those of the genus Camellia. The curvatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
(18 reference statements)
1
20
0
Order By: Relevance
“…For instance, exposure of in vitro growing pollen tubes to macroscopic electric fields has shown that those of the species Impatiens , Camellia japonica , Erythrina , tomato, tobacco and tulip grow towards the anode 20 21 22 , whereas those of Vinca , Narcissus , Lycoris , Hedychium and Eriobotrya grow towards the cathode 21 23 24 . Other species such as Gladiolus do not exhibit any tropism 20 . Depending on the experimenter, lily pollen tubes seemed to align with the field lines of an applied electric field 25 , or not at all 20 .…”
mentioning
confidence: 99%
“…For instance, exposure of in vitro growing pollen tubes to macroscopic electric fields has shown that those of the species Impatiens , Camellia japonica , Erythrina , tomato, tobacco and tulip grow towards the anode 20 21 22 , whereas those of Vinca , Narcissus , Lycoris , Hedychium and Eriobotrya grow towards the cathode 21 23 24 . Other species such as Gladiolus do not exhibit any tropism 20 . Depending on the experimenter, lily pollen tubes seemed to align with the field lines of an applied electric field 25 , or not at all 20 .…”
mentioning
confidence: 99%
“…1 It has also been shown that the electrotropic response in Camellia pollen tubes is mediated by calcium ion concentrations. 2 It has also been suggested that similar voltage readings in charophyte may be caused by the flux of acidic and basic ions, although this is controversial. 3 4 Even pure water can conduct acidic positively-charged protons by the Grotthuss mechanism.…”
Section: Discussion With Reviewersmentioning
confidence: 99%
“…Looking at actual twigs, I estimate the twig diameter to be 3/16" or .48 cm. This calculates to be a cross sectional area of 0.178 cm 2 . So the two orders of magnitude factor is reduced to 20.…”
Section: Answermentioning
confidence: 99%
“…Depending on plant species, exogenous electric fields affect the tube growth by directing the apical tube toward the cathode [Marsh and Beams, 1945;Zeijlemaker, 1956;Nakamura et al, 1991] or toward the anode [Wang et al, 1989].…”
Section: Introductionmentioning
confidence: 99%
“…Other investigations showed that the pollen tube growth direction is affected by an endogenous electric field (DC) [Weisenseel et al, 1975;Weisenseel and Jaffe, 1976;Cooke and Racusen, 1986;Obermeyer et al, 1992]. Depending on plant species, exogenous electric fields affect the tube growth by directing the apical tube toward the cathode [Marsh and Beams, 1945;Zeijlemaker, 1956;Nakamura et al, 1991] or toward the anode [Wang et al, 1989].…”
Section: Introductionmentioning
confidence: 99%